2020
DOI: 10.1109/access.2020.2975357
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Network Perspective of Innovation Diffusion: An Information-Behavior Framework

Abstract: Information transmission of innovation and peer effect among firms have significant impacts on innovation adoption decisions of firms, but those effects usually depend on the different types of inter-firm networks. Therefore, the diffusion of innovation (DOI) can be regarded as a process occurring in complex systems composed of different types of interactions, which can be categorized into links belonging to different layers of multiplex networks. This study aims to shed light on the complexity of innovation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Another aspect that affects percolation in a multiplex network is the structure of each layer. Yu et al (2020) compared ER, SF, and SW random networks as different layers of a duplex (two-layer) diffusion network. This concept has also been generalized to multilayer networks, comparing structures of random graphs as they affect information diffusion (Wang et al 2013).…”
Section: 11mentioning
confidence: 99%
“…Another aspect that affects percolation in a multiplex network is the structure of each layer. Yu et al (2020) compared ER, SF, and SW random networks as different layers of a duplex (two-layer) diffusion network. This concept has also been generalized to multilayer networks, comparing structures of random graphs as they affect information diffusion (Wang et al 2013).…”
Section: 11mentioning
confidence: 99%
“…With the development of innovation ecosystem and innovation network (Nylund et al, 2019;Yu et al, 2020), innovation subjects cooperate to carry out open innovation, or cross-border disruptive innovation, they provide more possibilities for the generation of new ideas. In the future, innovative ideas based on the flow and application of interdisciplinary knowledge and information may subvert the whole industry.…”
Section: Generation Of Disruptive Innovative Ideasmentioning
confidence: 99%
“…The results showed that the formation of people's green consensus is closely related to the dissemination of green information, and the dissemination of green information in turn promotes the adoption of green behaviors. Literature [13] pointed out that in the process of innovation diffusion, individuals make adoption decisions based on the information they have obtained, and the influence of information transfer between individuals on innovation adoption behavior is particularly important. Literature [14] proposed an optimal strategy model for epidemics by considering interactions between individuals and the impact of online emotional information on human behavior, striving to minimize the infection burden on the health care system and the financial loss of economic activity during the lockdown.…”
Section: Introductionmentioning
confidence: 99%